Good governance in Arab countries : between aspirations and reality, a study of selected models. - Hassan, Haider Kashkoul (The International and Political Journal, 2025)
It has witnessed many diverse categories in development and progress, negative or positive, this was reflected in reality that actually began from the supposed aspirations through the economic situation and the difference in income assistance, then the development in technology which was reflected in all aspects of life. Therefore, some societies live a comfortable and secure life, while other societies live below the poverty line and countries lack sovereignty because they are a stage for foreign interventions and do not have the ability to protect their borders and sovereignty. The decisive factor in the case of countries is effective and sound governance, which is the sail that controls the fate of the state and society through creating sustainable development that elevates the reality of the state and leads it towards societal peace. Therefore, it became necessary for the researcher to study political systems with good governance that were able to coincide with development, progress and political stability, and other countries that did not deal with good governance and governance in its imposed form. This led it to adopt wrong policies that cost it a lot in weakening the state’s condition, including illiteracy rates, poverty, weak technological incubator in the state, and many other consequences. The researcher adopted models of governance that would not rise to the level of good governance, such as the countries of Lebanon and Yemen. Another model contradicts the previous one, models that adopted the successful model of good governance in managing the state, represented by two models of countries, namely the Kingdom of Saudi Arabia and Qatar.